1984
DOI: 10.3109/01050398409076253
|View full text |Cite
|
Sign up to set email alerts
|

A Probe Earmold System for Measuring Eardrum SPL Under Hearing-AID Conditions

Abstract: A miniature probe-microphone assembly for use with earmolds was developed to measure the sound pressure level (SPL) of a signal at the eardrum under hearing-aid conditions. The probe-earmold (PE) system was designed with the earmold as an integral part of the acoustic measurement system so that no part of the probe itself projects into the ear canal. Data obtained during a previous investigation with an ear simulator indicated that the PE system could be used to measure eardrum SPL accurately (+/- 3 dB) up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Such variations in SPL are therefore dependent on the position of the probe microphone relative to the TM ͑Gilman and Dirks, 1986;Chan andGeisler, 1990͒. Gilman andDirks ͑1984͒ demonstrated that, when a probe microphone is placed at a fixed insertion depth, marked frequency-dependent differences in SPL will occur due to individual variations in earcanal length. The purpose of the current study was to examine two different approaches to quantifying in-situ probemicrophone measurements at frequencies above 4 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…Such variations in SPL are therefore dependent on the position of the probe microphone relative to the TM ͑Gilman and Dirks, 1986;Chan andGeisler, 1990͒. Gilman andDirks ͑1984͒ demonstrated that, when a probe microphone is placed at a fixed insertion depth, marked frequency-dependent differences in SPL will occur due to individual variations in earcanal length. The purpose of the current study was to examine two different approaches to quantifying in-situ probemicrophone measurements at frequencies above 4 kHz.…”
Section: Introductionmentioning
confidence: 99%